(untitled) (Nigerian Journal of Physiological Sciences, 2020)
The effects of intramuscular (IM) administrations of 10mcg/kg dexmedetomidine, followed 10 minutes later by either IM injection of 10mg/kg ketamine alone (DK) or with 2.5 mg/kg furosemide (DKF) were assessed in five healthy cats (3 males and 2 females) using selected anaesthetic indices (Time to onset of anaesthesia (OA), Duration of Analgesia (DA), Duration of Recumbency (DR), and Time to Standing (TS), as well as, changes in heart rate (HR), respiratory rate (RR) and rectal temperature (RT) , following loss of righting reflex, and at 10 min intervals for 60-minute. The OA for DKF group (2.2 ±0.45 min) was not significantly (P>0.05) different from that for DK group (2.4± 1.14 min). The DA (42.6 ±13.01min) and DR (71.6 ±17.94min) for DKF group were longer than respective values of DA (31.8± 14.3) and DR (51.2 ± 16.2min) for the DK group. The TS for DKF (3.6 ± 2.8 min) was shorter than TS (8.0±3.8) for DK. However, these differences were not statistically significant (P ˃ 0.05). HR, RR and RT were from 84.8 ± 8.7 to 113.2±30.7 beats/min, 17.4± 6.2 to 48.8 ±12.1 breaths/min and from 36.0±0.5 to 37.6 ± 0.6°C (DKF); 96.0±19.4 beats/min, 24.8±19.1 to 71.2 ± 34.3breaths/min and from 35.1±1.2 to 37.6 ±0.8 °C. There were no significant differences (P ˃ 0.05) in the vital parameters between the DKF and DK treatments. The values for HR and RR for DKF were generally lower than those for DK group. It was concluded that concurrent administration of furosemide with dexmedetomidine- anaesthesia in cats prolonged the duration of analgesia and recumbency but had no effect on onset of anaesthesia. A cat on this anaesthetic combination concurrently placed on furosemide medication will therefore need to be carefully monitored until full recovery